Crystallography of the low angle lamellar band boundaries in ARB-processed aluminum sheet - Quadir, Md Zakaria; Ferry, M.; Munroe, P. (2012)
Lamellar bands are the primary structural features in accumulative roll bonding (ARB) of sheet metals. The structural refinement in ARB sheets occur by forming a dense distribution of lamellar band boundaries. The lamellar band boundaries initiate as low angle interfaces, parallel to the existing lamellar band boundaries, irrespective of the crystallographic orientations of the parent lamellar bands. From an extensive investigation it was found that the transverse directions across the lamellar band boundaries are rotated by an angle equal to their misorientations. Such a phenomenon is not sustained when the boundaries turn to high angle. © (2012) Trans Tech Publications, Switzerland.